Power Quality Issues in Railway Electrification - Rajshree S, Thorat; Deshpande, MM (International Journal of Computer Sciences and Engineering, 2025)
This paper presents a perspective on power quality issues through railway electrification development and the necessity of power quality and system requirements for appropriate power quality. It has been a major problem in railway networks because of their special characteristics. The most important systems affected by railway electrification are upstream power supply networks railroad signaling and communication, and telecommunication systems. The most important problem is, in the case of three-phase systems, the imbalance of current because a railway load is nowadays always a single-phase load which causes a negative-sequence component (NSC) current equal to the positive-sequence component (PSC). In a high-speed train application, the modularized traction converter produces the significant harmonic currents caused from the switching behavior of a power converter. . One way to minimize the interference is to design the secondary windings of a power transformer decoupled magnetically as possible.